Infections After the Earthquake Disaster - Gulhadiye Avcu (Journal of Pediatric Research, 2023)

(untitled)
Earthquakes are among the most frequent natural disasters, responsible for approximately 1.87 million deaths in the 20th century. A magnitude-7.8 earthquake hit southeastern Turkey and parts of Syria in the early morning of February 6th, 2023. Earthquakes damage hospitals and healthcare facilities and lead to reduced emergency capacity. Such situations worsen the physical and mental health conditions of injured individuals. The incidence of infections due to injuries/trauma, water and foodborne infections, and acute respiratory infections were reported. Herein, we reviewed the infections among susceptible individuals, which may more easily develop in this area.